Cloning and sequencing of the Tnfa genes of three inbred mouse strains - Iraqi, F.A.; Teale, A.J. (Springer, 1997)
The C57BL/6 BALB/c and A/J inbred laboratory mouse strains often express different response phenotypes when challenged with a variety of infectious agents (Morrison et al. 1978; Bradley 1977; Hormmaeche et al. 1985). In view of the pivotal role of tumor necrosis factor Tnfa in innate immunity, we determined the nucleotide sequence of genomic Tnfa DNA of these three mouse strains. Genomic DNA of the three mouse strains C57BL/6, BALB/c, and A/J was obtained from the Jackson Laboratory (Bar Harbor, ME). The DNA was amplified by the polymerase chain reaction (PCR; Seiki et al. 1988) with primers designed from the promoter and the 3' untranslated (UTR) regions of the published sequence of the C57BL/6 Tnfa gene (Semon et al. 1987). The PCR amplifications were carried out as described earlier (Maga and Richarson 1991). Figure 1 shows the PCR amplification products of the genomic DNAs of the three mouse strains. The amplified products were of the expected size [(approximately 3800 base pairs (bp)]. The PCR-amplified DNAs were cloned in the pMOS vector, using the pMOS Blue T-vector Kit (Amersham, Little Chalfont, England). The nucleotide sequence of the cloned DNA was determined on both strands of each product with the ficomole Sequencing Kit (Strategene, La Jolla, CA). The complete DNA sequences of the clones were determined using internal primers for sequencing reactions based on the published sequence of the mouse Tnfa gene. The complete DNA sequence of the Tnfa genes of the three mouse strains is illustrated. A number of sequence polymorphisms are apparent at different locations in the genes. Point mutations were found in the introns and exons. A major polymorphism differentiating all three mouse strains was revealed in the microsatellite (AC)n located in the promoter region. [This microsatellite was referred to as a poly (A) repeat by Semon and co-workers (1987)]. A 4 bp deletion was found in the first intron in the A/J strain by comparison with the BALB/c and C57BL/6, while a 3 bp deletion was found in the first intron in the C57BL/6 by comparison with the A/J and BALB/c sequences. A single point mutation in each of the first two exons differentiated the A/J from the other two strains. These mutations would specify Ile in the first exon and Thr in the second exon of the A/J gene and Thr and Ala in these exons, respectively, in the BALB/c and C57BL/6 strains. The polyadenylating signal and the TTATTTAT elements in the 3'UTR, which have been reported to reduce the stability of the mRNA (Shaw and Kamen 1986), are conserved among the three strains.